Drug-induced tolerant persisters in tumor: mechanism, vulnerability and perspective implication for clinical treatment - Shujie Liu; Anfeng Jiang; Faqing Tang; Minghao Duan; Bin Li (Molecular Cancer)
Abstract Cancer remains a significant global health burden due to its high morbidity and mortality. Oncogene-targeted therapy and immunotherapy have markedly improved the 5-year survival rate in the patients with advanced or metastatic tumors compared to outcomes in the era of chemotherapy/radiation. Nevertheless, the majority of patients remain incurable. Initial therapies eliminate the bulk of tumor cells, yet residual populations termed drug-tolerant persister cells (DTPs) survive, regenerate tumor and even drive distant metastases. Notably, DTPs frequently render tumor cross-resistance, a detrimental phenomenon observed in the patients with suboptimal responses to subsequent therapies. Analogous to species evolution, DTPs emerge as adaptative products at the cellular level, instigated by integrated intracellular stress responses to therapeutic pressures. These cells exhibit profound heterogeneity and adaptability shaped by the intricate feedforward loops among tumor cells, surrounding microenvironments and host ecology, which vary across tumor types and therapeutic regimens. In this review, we revisit the concept of DTPs, with a focus on their generation process upon targeted therapy or immunotherapy. We dissect the critical phenotypes and molecule mechanisms underlying DTPs to therapy from multiple aspects, including intracellular events, intercellular crosstalk and the distant ecologic pre-metastatic niches. We further spotlight therapeutic strategies to target DTP vulnerabilities, including synthetic lethality approaches, adaptive dosing regimens informed by mathematical modeling, and immune-mediated eradication. Additionally, we highlight synergistic interventions such as lifestyle modifications (e.g., exercise, stress reduction) to suppress pro-tumorigenic inflammation. By integrating mechanistic insights with translational perspectives, this work bridges the gap between DTP biology and clinical strategies, aiming for optimal efficacy and preventing relapse.